Prevalence and pattern of drug resistance mutations among antiretroviral-treated HIV-1 patients with suboptimal virological response in Malaysia - Tee, K.K.; Kamarulzaman, A.; Ng, K.P. (2006)
To assess the prevalence of major drug resistance mutations in antiretroviral (ARV)-treated patients with detectable viral load (VL) in Kuala Lumpur, Malaysia, genotypic resistance testing was performed among treated human immunodeficiency virus type 1 (HIV-1) patients attending the University Malaya Medical Center between July 2003 and November 2004. The reverse transcriptase (RT) and protease genes from 36 plasma samples with detectable VL were examined for major mutations associated with ARV resistance as reported by the International AIDS Society-USA Drug Resistance Mutations Group. The prevalence of patients with at least one major mutation conferring drug resistance to nucleoside RT inhibitors (NRTIs), non-NRTIs (NNRTIs) or protease inhibitors (PIs) was 77.8. In the RT gene, the frequency of mutations associated with NRTIs and NNRTIs resistance was 52.8 and 63.9, respectively, with M184V and K103N mutations being selected most frequently by these drugs. A patient with Q151M mutation complex was also detected. Twenty-two percent of the patients had mutations associated with PIs. The following pattern of prevalence of ARV-resistant HIV-1 variants was observed: NNRTI-resistant > NRTI-resistant > PI-resistant. The prevalence of major drug resistance mutations among ARV-treated patients with detectable VL is high in Kuala Lumpur. Genotypic drug resistance testing is therefore important for monitoring patients experiencing ARV regimen failure.